Is not workplace gossip bad? The effect of positive workplace gossip on employee innovative behavior - Dai, Yuping; Zhuo, Xiangzhi; Hou, Jie; Lyu, Bei (Frontiers in Psychology, 2022)
Purpose - The purpose of this study is to examine the role of positive workplace gossip(PWG) in employees’ innovative behavior (EIB), whereby a mediating effect of employee loyalty (EL) is proposed in this relationship. The moderating effect of organizational trust (OT) is also examined on the indirect of PWG on EIB through EL. Design/methodology/approach - This research used a survey data of 327 employees from the enterprises selected from the Pearl River and Yangtze River Delta region of China. Based on the literature review, six main hypotheses were formulated and explored. The SPSS-Process Macro Plugin was used to analyze the hypothesized model. Findings - Results show there is a positive and significant relationship between PWG and EIB. This study also confirm that EL is an intervening variable and OT as a moderator. Practical implications - Organizations should pay more attention to workplace gossip phenomena, encourage employees to take appropriate part in positive workplace gossip and to communicate positive information about other colleagues frequently, and build an inclusive, open, sincere, and interdependent platform in the organization. Originality/Value - Employees innovative behavior plays an essential role in organization’s survival and development. Few studies have investigated the positive workplace gossip may promote employees innovative behavior through employee loyalty.The data, model, and findings of this research address the gap and add to the current state of knowledge.